(3GdCOhjI GdeVehfIs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd Mfjf (B: (3bGd LGdjfhS ai GdCOhjI GdeVhfI Cf GdfGQ GdJi CJJ Ydi Gdgjcd CMQbJ cJH GdCWHGA hCMQbJ di efgG cJHkG cKjQI cJGH ajg eLQjGJ cKjQI cfJ CNPJgG ef bhe aVdGA eLQHjf s
(3BNQgG (B:s
(3hEdi Gddg CQZH ai GdeYhfg Ydi eG jbQH Edjg hgh GdeSJYGf hYdjg GdJcdGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B23 - (3U(B33s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(2/851) s
Keywords: (3GdWHs